Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

-11 + 2r = 5r - 6 - 5


Sagot :

Answer:

x = 0

Step-by-step explanation:

First we need to move either 5r or 2r to the other side, in order to isolate the variable.

We'll move 5r, in this case, by subtracting it from 2r. Now we got: -11 - 3x = -6 - 5.

Next we subtract 5 from -6 to get

-11 - 3x = -11.

Now we can add 11 on both sides to get -3x = 0.

Finally divide by -3 to get x = 0.

Hope this helps :)

Answer:

Step-by-step explanation:

-11 + 2r = 5r - 6 - 5                  combine like terms

-11  +2r = 5r -11 .                       pass the 2r to the other side and it will become                                                                                                                      

         ⤻                                   negative  

-11 = 5r -2r -11                          combine like terms

-11= 3r - 11                               pass the -11 to the other side and now it will        

           ⤾                                 become positive

-11 +11 = 3r                               combine like terms

0 = 3r                                       divide both sides by three

0 = r                                         And then you will get your answer  :)